THE EFFECT OF JOB SATISFACTION, LEARNING AGILITY AND RESILIENCE ON PERFORMANCE WITH WORK STRESS AS AN INTERVENING VARIABLE IN SALES DEPARTMENT EMPLOYEES OF PT BUNGASARI FLOUR MILLS INDONESIA DURING THE COVID-19 PANDEMIC - Rahardi, Didit; Beti Nurbaiti; Achmad Fauzi (Dinasti International Journal of Management Science, 2022)
The research, which was conducted on 40 employees of the Sales Department of PT Bungasari Flour Mills Indonesia, aimed to see the effect of job satisfaction, learning agility and resilience on performance with work stress as an intervening variable. The research design and analysis of research results were processed using the structural equation model (SEM) – Smart PLS version 3.3.6. The results showed that (1) There was a direct effect of job satisfaction on performance (PValues < 0.05, which is 0.006) and resilience to work stress (PValues <0.05, which is 0.037), (2) There was no direct effect of resilience on performance (PValues > 0.05). ), (3) There is no indirect effect of job satisfaction, learning agility and resilience on performance through work stress (PValues > 0.05).